Highly sensitive single-fibril erosion assay demonstrates mechanochemical switch in native collagen fibrils - Flynn, Brendan P. (2012)
It has been established that the enzyme susceptibility of collagen, the predominant load-bearing protein in vertebrates, is altered by applied tension. However, whether tensile force increases or decreases the susceptibility to enzyme is a matter of contention. It is critical to establish a definitive understanding of the direction and magnitude of the force versus catalysis rate (k(C)) relationship if we are to properly interpret connective tissue development, growth, remodeling, repair, and degeneration. In this investigation, we examine collagen/enzyme mechanochemistry at the smallest scale structurally relevant to connective tissue: the native collagen fibril. A single-fibril mechanochemical erosion assay with nN force resolution was developed which permits detection of the loss of a few layers of monomer from the fibril surface. Native type I fibrils (bovine) held at three levels of tension were exposed to Clostridium histolyticum collagenase A. Fibrils held at zero-load failed rapidly and consistently (20 min) while fibrils at 1.8 pN/monomer failed more slowly (35–55 min). Strikingly, fibrils at 23.9 pN/monomer did not exhibit detectable degradation. The extracted force versus k(C) data were combined with previous single-molecule results to produce a “master curve” which suggests that collagen degradation is governed by an extremely sensitive mechanochemical switch.